THE INFLUENCE OF SERVICE QUALITY AND PHYSICAL EVIDENCE ON REVISIT INTENTION: A LITERATURE REVIEW - Dwi Wahyu Rusdianita; Mirrah Samiyah; Ansarul Fahrudda (Journal of Public Health Science, 2025)
This literature review aims to examine the influence of service quality and physical evidence on revisit intention in healthcare settings. As patient loyalty becomes increasingly critical in competitive health service markets, understanding non-medical service factors is essential. This review systematically analyzes 20 empirical journal articles published between 2016 and 2024, focusing on how tangible environmental elements and frontline service delivery affect patients' likelihood of returning to the same healthcare facility. Data were collected from journal databases using keywords such as "service quality," "physical evidence," and "revisit intention." Most of the reviewed studies used quantitative methods, applying statistical tools such as PLS-SEM and multiple regression analysis. Results show that service quality—particularly empathy, assurance, and responsiveness—has a consistently strong positive effect on revisit intention. Physical evidence, including facility cleanliness, layout, and comfort, also influences revisit behavior, although its impact varies depending on context. This review highlights the need for hospitals to improve both environmental and interpersonal service dimensions to enhance patient retention. Limitations include a focus on selected studies and potential publication bias. Future research should explore moderating variables and conduct longitudinal or comparative studies.